2019
DOI: 10.1016/j.tranon.2019.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Building CT Radiomics-Based Models for Preoperatively Predicting Malignant Potential and Mitotic Count of Gastrointestinal Stromal Tumors

Abstract: PURPOSE: To build radiomic prediction models using contrast-enhanced computed tomography (CE-CT) to preoperatively predict malignant potential and mitotic count of gastrointestinal stromal tumors (GISTs). PATIENTS AND METHODS : A total of 333 GISTs patients were retrospectively included in our study. Radiomic features were extracted from the preoperative CE-CT images. According to postoperative pathology, patients were categorized by malignant potential and mitotic count, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 45 publications
1
42
0
Order By: Relevance
“…In this study, size and cystoid variation of CT signs and meanValue of texture parameters, which were most Note: Size: the maximal diameter on the largest cross section of tumor; * Values refer to median (interquartile range (IQR)); P-values were the results of univariable association analyses of each characteristic and of the two groups; SD standard deviation; Pre-score prediction score associated with the malignant potential of GISTs, were selected to establish the prediction nomogram. Tumor size has been confirmed to be positively correlated with the malignancy of GISTs [29][30][31]. The maximal diameter on the largest cross section of tumor in highmalignant potential GISTs was larger than that in lowmalignant GISTs in both the training and validation sets (p values < 0.001, respectively) (Table 3), the results of this study are consistent with the conclusion of the above reports.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In this study, size and cystoid variation of CT signs and meanValue of texture parameters, which were most Note: Size: the maximal diameter on the largest cross section of tumor; * Values refer to median (interquartile range (IQR)); P-values were the results of univariable association analyses of each characteristic and of the two groups; SD standard deviation; Pre-score prediction score associated with the malignant potential of GISTs, were selected to establish the prediction nomogram. Tumor size has been confirmed to be positively correlated with the malignancy of GISTs [29][30][31]. The maximal diameter on the largest cross section of tumor in highmalignant potential GISTs was larger than that in lowmalignant GISTs in both the training and validation sets (p values < 0.001, respectively) (Table 3), the results of this study are consistent with the conclusion of the above reports.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, CTbased predictive nomogram in discriminating malignant potential of GISTs could have better generalizability and clinical application value. Previous research has shown that quantitative features extracted from CT images might be a potential imaging biomarker for mitotic count of GISTs in a noninvasive way [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiomics can extract hundreds of quantitative features from medical images and is promising in prediction the biological behavior on the onset of tumor. In a number of previous studies, radiomics has been implicated in the predictions of the biological behaviors in GISTs [19–21]. Two studies used radiomic features extracted from CE‐CT to build prediction models for predicting malignant potential with promising accuracy [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Recently Radiomics prediction model has gained attention in the diagnosis of cancers [17,18]. Previous studies have shown high accuracy of radiomics in the assessment of biological behavior of GISTs comprehensively, including malignant potential [19,20], mitotic rate [19], recurrence [21]. However, to the best of our knowledge, this is the first ever study that investigates whether radiomics can be used as a tool to assess Ki‐67 expression status in GISTs.…”
Section: Introductionmentioning
confidence: 99%